Artificial Intelligence in Educational Governance: A Risk-Based Ethical Framework for Strengthening Religious Moderation in Indonesia - Ahmad Imam Khairi; Sugiantoro; Kacung Wahyudi; Itaanis Tianah; Salman Al Farisi (re-JIEM (Research Journal of Islamic Education Management), 2026)
The digital transformation of education in Indonesia has evolved from basic service digitization toward data-driven governance increasingly reliant on artificial intelligence. While the integration of artificial intelligence in educational governance promises administrative efficiency and optimized decision-making, it simultaneously raises ethical concerns related to algorithmic bias, accountability, transparency, and the potential erosion of humanistic educational values. This study aims to critically analyze the ethical implications of artificial intelligence deployment in Indonesian educational governance and examine its relevance to strengthening religious moderation as a strategic national education agenda. The research employs a qualitative approach using a critical literature review design combined with policy analysis. Data were drawn from reputable scholarly publications, international policy frameworks, and national regulations concerning digital transformation and religious moderation. The analysis proceeded through thematic identification, normative evaluation grounded in principles of algorithmic justice and human-centered governance, and contextual synthesis within Indonesia’s plural socio-religious landscape. The findings indicate that without a robust ethical framework, artificial intelligence-driven governance risks reproducing structural inequalities and narrowing pluralistic dialogue. This study proposes a conceptual ethical governance model aligned with religious moderation, emphasizing risk mapping, ethical design protocols, meaningful human oversight, public accountability mechanisms, and continuous evaluation. The model offers a normative and operational reference for policymakers and educational institutions to ensure that digital transformation remains aligned with justice, inclusivity, and social cohesion.